2016
DOI: 10.1638/2015-0162.1
|View full text |Cite
|
Sign up to set email alerts
|

PROPOSED SIMPLE METHOD FOR ELECTROCARDIOGRAM RECORDING IN FREE-RANGING ASIAN ELEPHANTS (ELEPHAS MAXIMUS)

Abstract: Electrocardiography represents a relevant diagnostic tool for detecting cardiac disease in animals. Elephants can present various congenital and acquired cardiovascular diseases. However, few electrophysiologic studies have been reported in captive elephants, mainly due to challenging technical difficulties in obtaining good-quality electrocardiogram (ECG) tracings, and no data are currently available for free-ranging Asian elephants (Elephas maximus). The purpose of this pilot prospective study was to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…They include wild animals such as brown bears from either a sanctuary or caught in the wild [14,15], lions and tigers [16,17]. They include large animals such as Asian elephant [18][19][20][21] and small animals such as guinea pigs [22,23]. Some animals are not readily available for study such as rhinoceros [24] and grizzly bears [25] because of the difficulty in capturing them for study.…”
Section: Resultsmentioning
confidence: 99%
“…They include wild animals such as brown bears from either a sanctuary or caught in the wild [14,15], lions and tigers [16,17]. They include large animals such as Asian elephant [18][19][20][21] and small animals such as guinea pigs [22,23]. Some animals are not readily available for study such as rhinoceros [24] and grizzly bears [25] because of the difficulty in capturing them for study.…”
Section: Resultsmentioning
confidence: 99%
“…This technique has been used and reported in many different ‘exotic’ species. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Due to the scant information on ECG references, it is rarely performed in turtles and tortoises. The MEA is the average of all the instantaneous mean electrical vectors that occur sequentially during depolarisation of the ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…Electrocardiography is a useful diagnostic tool for heart diseases. This technique has been used and reported in many different ‘exotic’ species 12–19 . Due to the scant information on ECG references, it is rarely performed in turtles and tortoises.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study revealed that an elephant's emotional state might be estimated by its heart rate and the heart rate measurement ratio change. In the past, an elephant's heart rate was recorded using electrocardiograms [2,3]. This study showed several advantages to alternatively using wearable heart rate measurement devices.…”
mentioning
confidence: 99%